On the formation of hydrogen-deficient low-mass white dwarfs - Battich, Tiara (2020)
Context. Two of the possible channels for the formation of low-mass (M⋆ ≲ 0.5 M⊙) hydrogen-deficient white dwarfs are the occurrence of a very-late thermal pulse after the asymptotic giant-branch phase or a late helium-flash onset in an almost stripped core of a red giant star. Aims. We aim to asses the potential of asteroseismology to distinguish between the hot flasher and the very-late thermal pulse scenarios for the formation of low-mass hydrogen-deficient white dwarfs. Methods. We computed the evolution of low-mass hydrogen-deficient white dwarfs from the zero-age main sequence in the context of the two evolutionary scenarios. We explore the pulsation properties of the resulting models for effective temperatures characterizing the instability strip of pulsating helium-rich white dwarfs. Results. We find that there are significant differences in the periods and in the period spacings associated with low radial-order (k ≲ 10) gravity modes for white-dwarf models evolving within the instability strip of the hydrogen-deficient white dwarfs. Conclusions. The measurement of the period spacings for pulsation modes with periods shorter than ∼500 s may be used to distinguish between the two scenarios. Moreover, period-to-period asteroseismic fits of low-mass pulsating hydrogen-deficient white dwarfs can help to determine their evolutionary history.